Procedural status of participants in criminal proceedings as a means of securing rights and legitimate interests - Solovyova, O. Ye. (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The concept of procedural status of participants in criminal proceedings is considered. According to the Criminal Code of Ukraine, participants in criminal proceedings are parties to criminal proceedings, persons who take part in criminal proceedings. A comparison of this definition with specific norms of the Criminal Procedure Code of Ukraine, which refer to participants in criminal proceedings, shows that the law includes not only persons involved in criminal proceedings, but also the subjects of criminal procedural activity themselves, i.e. officials and bodies that conduct (investigate) criminal proceedings, etc. The procedure for recognizing a person as a subject of criminal procedural relations established by law is of great importance for ensuring the legality of criminal proceedings and allows to properly protect the interests of persons involved in this field of activity. Ambiguity of understanding and extended interpretation of the reasons for involvement in criminal proceedings, failure to establish a clear procedure for acquiring the relevant status violate the orderliness of procedural activities, which thus reflects on the legitimate interests of the participants in criminal proceedings. Therefore, a formal approach to determining the circle of participants in criminal proceedings should be followed. This approach is able to give such positive results as certainty, stability of the procedural provision, predictability of the behavior of participants in criminal proceedings and the results of their actions, as well as to create a logical and consistent system of mechanisms for the exercise, protection and protection of their rights and legitimate interests.